Crew on foredeck of whaling schooner Era, Hudson Bay, Canadian Arctic - Comer, George (Creator) (Ownership Statement: Mystic Seaport, 1897)
Crew members are apparently at work on the foredeck of the whaling schooner Era at Hudson Bay, Canadian Arctic, ca. 1897-1905. Infrastructure Livelihood Title supplied by cataloger. Information from original envelope identifies this as Photo 157. The schooner Era was built in 1847 at Boston, Massachusetts. She was a New London whaling vessel until her last voyage out of that port in 1892; her masters included James Monroe Buddington, John O. Spicer, and George Comer. She was wrecked off Miquelon Island, July 27, 1906. Taken by Captain George Comer (1858-1937), a sealer and whaling captain from East Haddam. He went to sea while still in his teens and was later master of vessels from both New London and New Bedford. Comer participated in voyages involved in polar expeditions and was noted for his studies of Arctic peoples and their environment.